Association of Metabolic Syndrome and Psoriasis - Tooba Malik, Saba Nasreen, Hira Shafquat Memon, Shakila Yousuf, Seemab Khan, Sana Gul (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to determine the association of metabolic syndrome and psoriasis Study Design: Case control study Settings: This study was conducted in Department of Dermatology in collaboration with Department of Chemical Pathology, PNS Shifa, Karachi. Duration of Study: Conducted for the duration of Six months from 1st July, 2020 to 30th December, 2020. Results: In our study, 67.39%(n=31) in cases and 76.09%(n=35) in Controls were between 20-35 years of age while 32.61%(n=15) in cases and 23.91%(n=11) in controls were between 36-50 years of age, mean+sd was calculated as 31.87+6.71 and 30.0+6.29 years respectively, 63.04%(n=29) in cases and 67.39%(n=31) in controls were male while 36.96%(n=17) in cases and 32.61%(n=15) in controls were females, frequency of association of metabolic syndrome and psoriasis was recorded as 56.52%(n=26) in cases and 32.61%(n=15) in controls had metabolic syndrome while 43.48%(n=20) in cases and 67.39%(n=31) in controls had no findings of metabolic syndrome, p value was calculated as 0.02 showing a significant difference. Conclusion: We concluded that the frequency of metabolic syndrome is higher among psoriasis cases when compared to the control cases. However, our significant results suggested that the physicians should periodically screen psoriatic patients for MetS and timely suggest medication or changes in lifestyle.